Mobiles for Development – A Comparative Analysis of Business Decisions. Issue 3 (3rd July 2022) - Scott, Nigel; Batchelor, Simon; Jones, Tom; Barnett, Inka; Gordon, Jessica; Faith, Becky
ABSTRACT: Much research on 'mobiles for development' focuses on outcomes and impact of services. This paper focuses on the underlying business models. It draws on two case studies as part of a UK Aid funded evaluation of the GSM Association led mNutrition programme. Vodafone Farmers Club in Ghana provides agricultural and nutrition information via SMS and Wazazi Nipendeni in Tanzania is a maternal and child health SMS service. The paper presents the salient points of the two contrasting business models, highlighting the strengths and weaknesses of both. The merits of the different approaches depend on the principle motivation, but when it comes to delivering positive outcomes among the poorest, the weight of evidence appears to be in favor of an independent, third party driven model.